Structural and functional characterization of the periplasmic cytochrome PpcA from Geobacter metallireducens - Portela, Maria do Pilar Castillo (2020)
The bacterium Geobacter metallireducens (Gm) is capable of transferring electrons to the cell’s exterior and thus reduce extracellular electron acceptors. Because of this, Gm has been used for electricity harvesting upon its association with electrodes and for bioremediation of contaminated waters with Cr(VI) and U(VI), for example, which serve as extracellular acceptors. The triheme c-type cytochrome PpcA from Gm is abundant in the periplasm and crucial for bridging the electron transfer between the cytoplasm and the cell’s exterior. It shares 80% of identity with the well-characterized PpcA from Geobacter sulfurreducens (Gs) but the functional properties, namely the reduction potential and the hemes’ order of oxidation, are markedly different. In this work, we have used nuclear magnetic resonance spectroscopy to structurally characterize PpcA from Gm and to probe pH-linked conformational changes in the reduced and oxidized states. The structural role of the highly conserved residue Val13 in the PpcA family of Gm and Gs was probed by replacing it with alanine, isoleucine, serine and threonine. Replacement of Phe6 and Trp45 in PpcA from Gm with the correspondent amino acids in PpcA from Gs – leucine and methionine – has been achieved to probe their influence in the reduction potential. The obtained results suggest that the structure in the reduced and oxidized states is conserved and similar to that of PpcA from Gs, with localized differences in the polypeptide segments near hemes I and III. Val13 has been shown to be essential for the maintenance of a single heme core conformation. The substitution of Phe6 and Trp45 yielded opposite effects on the cytochrome’s reduction potential values, suggesting that these residues play different roles in the modulation of this property. These observations emphasize the preponderant role of key residues in the structure of PpcA from Gm and in the fine-tuning of its reduction potential values.